2017
DOI: 10.15405/epsbs.2017.09.5
|View full text |Cite
|
Sign up to set email alerts
|

Zataria Multiflora Boiss Improves Learning And Memory Impairment Induced By Toxoplasma Gondii Infection

Abstract: Recent epidemiological and experimental studies also showed that latent toxoplasmosis can lead to a number of neurological and behavioral disorders such as learning and memory impairments. Recent studies showed that the essential oil and methanolic extract of the Zataria multiflora revealed a significant anticholinesterase activity on in vitro ().Here, we evaluated the effect of Z. multiflora essential oil to ameliorate learning and memory impairments induced by T. gondii infection in BALB/c mice. The animal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…At present, there are a restricted number of agents for the treatment of toxoplasmosis and the combination of pyrimethamine and sulfadiazine is the most common (3). However, these drugs may results in some adverse effects, including osteoporosis, sepsis and also teratogenic effects particularly in persons with immunocompromised patients (2,3). So far, efforts to decrease the toxicity of these compounds have been failed, that reinforces the requirement for novel anti-Toxoplasma drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are a restricted number of agents for the treatment of toxoplasmosis and the combination of pyrimethamine and sulfadiazine is the most common (3). However, these drugs may results in some adverse effects, including osteoporosis, sepsis and also teratogenic effects particularly in persons with immunocompromised patients (2,3). So far, efforts to decrease the toxicity of these compounds have been failed, that reinforces the requirement for novel anti-Toxoplasma drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasma gondii is a universal prevalent protozoan parasite which infected all the warm-blooded animals such as humans (1). Human, usually, can be infected via three chief ways of transmission: consumption of tissue cysts in infected meat, consumption of food or water contaminated with oocysts and congenitally (2,3). Toxoplasmosis in immunecompetent persons is seldom symptomatic.…”
Section: Research Paper Introductionmentioning
confidence: 99%
“…For example, it has been demonstrated that female BALB/c mice infected with the ME49 strain of T. gondii, but not the Prugniaud strain, exhibit impaired spatial working memory at 2 months post-infection [205]. Overall though, the limited literature points toward spatial learning, working memory, and short-term memory being impaired in murine models due to T. gondii infection [203][204][205]208].…”
Section: Functional Consequences Of T Gondii Infectionmentioning
confidence: 99%
“…Memory and learning changes have received little attention in the literature compared to other behavioral modalities, and the murine studies that have been conducted report inconsistent results [ 202 , 203 ]. These inconsistencies may be attributed to differences in parasite strain, cyst burden, behavioral paradigm, rodent species, sex, and post-infection time of testing [ 204 207 ].…”
Section: Toxoplasma Gondiimentioning
confidence: 99%
See 1 more Smart Citation